Pelaksanaan Peraturan Gubernur Bali Nomor 97 Tahun 2018 Tentang Pemakaian Kantong Plastik Sekali Pakai di Kota Denpasar - Gede Putu Oka Brahma Adhi; I Wayan Rideng; Ida Ayu Putu Widiati (Warmadewa Press, 2021)
The community and the Government of Denpasar City took the initiative to save Bali Island, which is known as the last paradise island,